The Effect of Earning Aggressivenesss on Stock Trading With Investor Sophistication and Asymmetry Information as Moderator - Ria, Ria; Murwaningsari, Etty (International Journal of Economics and Financial Issues, 2018)
This study aims to examine the effect of earning aggressivenesss on stock trading with investor sophistication and information asymmetry as moderator. This research uses quantitative method with regression analysis model by stratified random sampling based on subsector strata in manufacturing company that go public in Indonesia Stock Exchange, with sample size of the company as 59 companies during the period of 2012-2016 (5 years). This study shows that earning aggressiveness significantly negatively influences the Mean Return Scale, but has a significant positive effect on Trading Volume Activity. The negative effect of earnings aggressiveness on Mean Return Scale is stronger in firms with high investor sophistication levels than firms with low investor sophistication levels, while the negative effect of earning aggressiveness on Trading Volume Activity is stronger in firms that investor sophistication level is high than in companies with low investor sophistication levels. The negative effect of earnings aggressiveness on Mean Return Scale is weaker in firms where the level of information asymmetry is high than in firms with low information asymmetry levels. While the negative effect of earnings aggressiveness on Trading Volume Activity is stronger in companies with high information asymmetry level than in companies with low information asymmetry level Keywords: earning aggressivenesss, stock trading, investor sophistication, information asymmetry JEL Classifications: E44, G1